Profile of Airway Patency, Respiratory Rate, PaCO2, and PaO2 in Severe Traumatic Brain Injury Patients (GCS - Maria Marind Desrianti Hutauruk; Ira Dharmawati; Philia Setiawan (Faculty of Medicine-Universitas Airlangga, 2019)
Introduction: Traumatic Brain Injury (TBI) is the most common neurotrauma with high morbidity and mortality. Many guidelines recommend the use of mechanical ventilation for severe TBI patients, but there are limited resources of procuring ventilator machine in hospitals especially in developing countries. Yet it is not comparable with the number of TBI patients. Objective: This study is purposed to provide the profile of ventilation and oxygenation (airway patency, RR, PaCO2, and PaO2) in severe TBI patients (GCS<9) admitted in the Emergency Room (ER) of Dr. Soetomo General Academic Hospital Surabaya. Method and Material: This is a retrospective study using medical records of patients with TBI who were admitted in the ER of Dr. Soetomo General Academic Hospital from January to December 2017. The patient's general characteristics, blood gas analysis (PaCO2, PaO2), airway patency were recorded and analyzed. Results and Discussion: Thirty-seven severe TBI patients were included in the analysis. 30 men (81.1%) and 7 women (18.9%) with an average of 37±16 years old (range: 5-65) were studied. Most of the patients (94.6%) had MAP between 60 and 160 mmHg, PaCO2<35 mmHg (72.9%), PaO2>60 mmHg (100%), RR>20 breaths per minute (70.2%), and patent airways (64.9%) with simple support of oxygen. 8.1% of all of those patients had PaCO2>45 mmHg. Conclusion: Most of the severe TBI admitted in the ER of Dr. Soetomo General Academic Hospital had hypocapnia or respiratory rate higher than the normal range. Though one-third of the patient has partial obstruction of the airway, no significant hypoxemia is found.